Costs of conservation of the three pilot marine protected areas of San Joaquin, Iloilo - Corvera, Jo Annie D (Miagao, Iloilo University of the Philippines Visayas, 2011)
The need to protect the remaining corals and seagrass of the Municipality of San Joaquin, Iloilo was addressed by establishing marine protected areas (MPA). This study seeks to determine the cost of establishing and maintaining the pilot of MPAs of San Joaquin. The study will also identify the effects, issues and problems at present. Data were gathered through personal interview and Focus Group Discussion (FGD). A total of 51 members of the MPA Management Board and Municipal Technical Working Group were interviewed. The local government unit of San Joaquin spent a substantial amount for MPA establishment. There are also unpaid labors coming from MPA volunteers. The stakeholders believe that there is an increase in fish abundance that they attribute to the establishment of MPA. Garbage, illegal and commercial fishing and siltation remains a threat to the coastal resources of municipality.
Special Problem (MMA) -- University of the Philippines Visayas, 2011.
Keywords: Marine protected areas -- San Joaquin, Iloilo